An Act for Raising the Revenue for the Next Fiscal Year, § 2, ALEXANDRIA GAZETTE, Jun. 15, 1876, at 2 (Alexandria, Virginia). - (:unkn) unknown (My University, 1876)
Imposed a 10 dollar tax on shooting galleries
Keywords: SHOOTING RANGES OR GALLERIES